Proximate composition, sugar profiles, minerals and carotenoids content and antioxidant capacity of momordica cochinchinensis L. Spreng or Gac (Vietnam) or Teruah (Malaysia) fruit fractions (peel, pulp, and aril) - Mohd Nazri AR; Amin I; Azrina A; Ahmad Fazli AA; Mohd Desa H; Nor Hayati, M (2022)
The proximates, sugar profiles, minerals, carotenoids, and antioxidant capacity of Momordica cochinchinensis L. Spreng or Gac (Vietnam) or Teruah (Malaysia) fruits fractions (peel, pulp, and aril); were evaluated. Results showed Gac aril to contain the significant highest carbohydrate (55.6g/100g); compared to the pulp (30.9g/100g) and peel (19.3g/100g). Meanwhile, Gac peel contained the highest protein (6.2g/100g) and dietary fibre (56.9g to 58.1g/100g). Glucose and fructose are present in Gac fruit. Glucose was the main type of sugar in both Gac pulp and aril, with a significant value of 6.66 g/100 g and 7.55 g/100 g, respectively. Meanwhile, fructose also detected in Gac pulp and aril amounted to 5.84 g/100 g and 6.45 g/100 g, respectively. Potassium was the most abundant mineral in the Gac peel (817.59 mg/100g), followed by pulp (658.20 mg/100g) and aril (228.79 mg/100g). Lycopene was the main carotenoid found in Gac aril (31.7 – 103.7 mg/g) followed by β-carotene (2.9 – 9.6 mg/g); astaxanthin, (1.54 – 4.91 mg/g); lutein, (0.16 – 1.35 mg/g) and zeaxanthin (0.35 – 1.49 mg/g) in the pulp. Antioxidant activities of Gac were found between 22.61% – 58.76%, 37.63% – 41.64% and 2.46% –19.66% in the gac peel, pulp, and aril, respectively, using the DPPH assay. In conclusion, Gac pulp and aril contained good sources of carbohydrates, minerals, lycopene, and β-carotene.